The Right Heart 2014
DOI: 10.1007/978-1-4471-2398-9_9
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricle and High Altitude

Abstract: At high altitude, as hypoxia induces pulmonary vasoconstriction and increases ipulmonary arterial pressure, right ventricular (RV) function will be affected. The right ventricular function may be affected directly by the hypoxaemic challenge or indirectly through a pressure overload due, in turn to changes in the pulmonary circulation. Both animal and human studies show that moderate or transient hypoxia results in adaptive changes in right ventricle that are reversible with re-exposure to normoxic conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…The left ventricle does not seem to be affected, except for a low proportion of aortic dilation, which could also be explained by the hyperdynamic state of this model. The latter findings agree with a previous report regarding left ventricle changes under hypoxia (Richalet and Pichon, 2014 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The left ventricle does not seem to be affected, except for a low proportion of aortic dilation, which could also be explained by the hyperdynamic state of this model. The latter findings agree with a previous report regarding left ventricle changes under hypoxia (Richalet and Pichon, 2014 ).…”
Section: Discussionsupporting
confidence: 94%
“…Likewise, this study also shows a striking proportion of RVWT enlargement, suggesting that in the long term, almost all subjects experience RV remodeling and that an mPAP value of 25 mmHg would be sufficient to generate significant changes in the right heart. Whether this is merely an acclimatization response in this model of exposure that causes the RV to increase its performance as a consequence of its homeometric adaptation to afterload increase (Kolár and Ostádal, 1991 ; Naeije and Dedobbeleer, 2013 ; Richalet and Pichon, 2014 ) and/or ROS activation by hypoxia of AMP kinase proteins (Chen et al, 2012 ; Waypa et al, 2016 ) or other mechanisms remains to be elucidated. Additionally, a vascular hyperdynamic state triggered by adrenergic activation and autonomic system imbalance must be considered for exerting its influence on the above variables and possibly in RV dilation (Richalet and Pichon, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 However, an imbalance among factors such as endothelial vasoconstrictors, vasodilators, reactive oxygen species, other molecules (e.g., insulin, asymmetric dimethylarginine (ADMA)), susceptibility, and genetic factors is clearly the cornerstone at the molecular level. 7,48,49 As has commonly been observed in the clinical setting, most responses are physiologically useful; however, in some cases, these beneficial responses are excessive and can be the source of a pathological response. The main examples of such cases are exaggerated polycythemia or CMS under chronic hypoxia and HPV leading to HAPH 12 (Fig.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Available studies that evaluated the effects of acute high-altitude exposure on the RV produced conflicting results (Naeije and Dedobbeleer, 2013 ; Richalet and Pichon, 2014 ). While some studies demonstrated an augmented RV function in response to acute hypoxia-induced afterload increase (Berger et al, 2018 ; Sareban et al, 2020 ), others found no change (Huez et al, 2005 ) or even an impaired RV function (Reichenberger et al, 2007 ; Hanaoka et al, 2011 ; Page et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%